(untitled) (Bangladesh Journal of Medical Science, 2016)
Background: Genetic factors play an important role in the determination of hypertensive disease in a family. The -344T/C the aldosterone synthase gene has been reported in various populations closely related to hypertension. The aim of this study was to determine the presence of the -344T/C polymorphism of the aldosterone synthase gene and the levels of plasma aldosterone in individuals with and without a family history of hypertension. Methods: This study was a case control design, with healthy individuals with a family history of hypertension as cases (n-42) and those without a family history of hypertension as controls (n=41). The subjects plasma aldosterone levels were analysed by enzyme-link immunosorbent assay (ELISA) and the gene polymorphism was analysed by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). The data were analysed by an independent sample T-test and Chi square test, and the significance level was set at P<0.05. Result: The frequency of the TT + TC genotype was higher in cases, and this increase was significant different compared to the controls (P<0.046). The frequency of the TT + TC genotype was 2.56 higher in cases than controls. The frequency of the C allele in cases was also significantly different compared to the controls (P = 0.039) and 2.29 more frequent in cases than the controls (P = 0.039). The plasma aldosterone level was 42.35 pg/dL in cases and 34.9 pg/dL in controls (P = 0.616). Plasma aldosterone level in cases with the CC, TC and TT genotypes were 48.29, 40.8 and 35.2 pg/dL, respectively (P = 0.774). Our study concludes that individuals with a family history of hypertension are at a higher risk of developing hypertension. Follow-up studies are required to determine the incidence of hypertension in a person with a family history of hypertension and who is a carrier of genetic risk factors. Bangladesh Journal of Medical Science Vol.15(3) 2016 p.435-440